PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Christopher Hadisurja; Prima Apriwenni (Jurnal Akuntansi, 2020)
The global economic crisis towards large companies has focused on the importance of GCG. The corporate governance mechanism will improve supervision for the company so that through supervision it is expected that the company's performance will be better and can affect the value of the company. Problems about the environment are also experienced in Indonesia because the environmental impact of industrialization in big cities has been considered to be at a dangerous level. Due to the increasingly complex problems regarding the environment lately, many companies are increasingly aware of the importance of implementing a Corporate Social Responsibility (CSR) program as part of a business strategy. The sampling technique used was purposive sampling method. The sample used was 45 LQ45 companies listed on the Indonesian Stock Exchange in 2015-2017 (for 3 years) with a total of 90 data. Based on the results of data analysis, this study concludes that the audit committee proved to have a significant positive effect on firm value. independent commissioners, managerial ownership is not proven to have a significant positive effect on firm value, while CSR is not proven to have a significant positive effect on firm value. Keywords: Audit Committee, Independent Commissioners, Managerial Ownership, and Corporate Social Responsibility, Firm Value